PRAWNE SKUTKI PRZEJAWÓW DEMORALIZACJI NIELETNICH NA PODSTAWIE BADAŃ AKT SĄDOWYCH - Kosek, Mirosław; Łazuga, Waldemar (Zeszyty Prawnicze, 2017)
Legal Consequences of Demoralization of Minors on the Basis of the Analysis of Court Files Summary The article discusses the results of the research performed by Waldemar Łazuga and presented in the master thesis entitled „The expressions of the demoralization of the minors in the context of the Act on the proceedings against the minors” written under a supervision of Prof. dr hab. Wanda Stojanowska in the Academy of Special Pedagogy in Warsaw in academic year 2001/2002 regarding the demoralization of minors and its complex context. The results were also analyzed and the conclusions on theirs basis were drawn.